Menguji Komitmen Badan Publik Dalam Pelaksanaan UU No. 14 Tahun 2008 Tentang Keterbukaan Informasi Publik Dalam Konteks Akuntabilitas Pemerintahan; Studi Kasus Komisi Informasi Provinsi Jawa Tengah - Prayitno, Budi (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2012)
The government's efforts to achieve good governance in accordance with public demand have been realized, by the issuance of Law no. 14 of 2008 on Public Information. Follow-up of the enactment of Law no. 14 In 2008 it was the establishment of the Public Information Committee at the central, provincial and regency / city. The fundamental reasons of public disclosure are none other than to encourage public bodies at all levels of an organization or unit is more transparent to the public (society). Moreover, the principle of transparency is a part of good governance. This study aims to determine the type of information requested by the community and what the barriers faced by those that took him to the realm of mediation and adjudication non-litigation at the Information Commission's Central Java province. The primary data used in this study is dispute information submitted to the Commission of Public Information of Central Java Province. Techniques of data collection conducted by an interview of Commissioner KIP to obtain further information regarding general dispute information submitted by the applicant as a community. The conclusion is still a lot of public bodies are not ready to fully open in providing information requested by the community. This is because the nature of the bureaucracy that had been closed. They also worry if the information requested by the public will be abused to their interests.